Employment Protection and the Market for Innovations - Andreas Bastgen; Christian Holzner (Center for Economic Studies and ifo Institute (CESifo), 2015)
We study the effects of employment protection taking into account that firms can invest in R&D or buy new technologies in order to restore their productivity. To do so we develop an equilibrium matching model with an imperfect labor and innovation market. If employment protection is introduced, firms' willingness to pay for product or process innovations increases. This shifts economic activity towards firms specializing in process and product innovation and triggers entry of new start-ups. We calibrate our model to match aggregate US labor and product market statistics and show that our model generates the estimated negative impact of wrongful dismissal laws in the US on productivity and the positive effect on the number of innovations and firms.
Keywords: J64; J65; O31; O38; 330; employment protection; firing costs; innovations; patents; productivity; market imperfections